BETWEEN AFFECTIONS AND FISHING:: Transgenerationality of traditional knowledge among fishing women in the Segredinho/Capanema-PA community (Interdisciplinary Studies Journal, 2024)
This article discusses the transgenerational aspects present in the development of artisanal fishing in the Segredinho community, which is located in the municipality of Capanema, in the State of Pará. The objective of the work was to understand the way in which traditional knowledge is focused on fishing artisanal and are seized by women from the same family and from different generations in that community. Thus, this research is configured in a qualitative research approach, with observation and interviews using a script with semi-structured questions, forming part of the techniques and instruments used in collecting information. As the main result, it was noticeable that the transfer of traditional knowledge occurs through experiences linked to the practice of artisanal fishing, where knowledge about instruments, fish habits, location in the lake, among others, are learned through observation and exchange of experience between fisherwomen, and the activity is essential for the subsistence of these women's families.
Keywords: Traditional Knowledge; Women; Artisanal Fishing; Transgenerationality